Monitoring type B buyer–supplier relationships. Issue 18 (17th September 2018) - Faraz, Alireza; Sanders, Nada; Zacharia, Zach; Gerschberger, Markus
Abstract : The ability to monitor supplier performance is a critical capability for maintaining strong buyer–supplier relationships. Monitoring type B suppliers is especially challenging as they are not as clearly defined as either type A, with strong strategic partnerships, or type C, with little partnership. This research develops a non-parametric multivariate Hoteling's T 2 control chart to capture the in-control state of a dyadic relationship (Phase I), and show how it would be developed based on survey data of buyer–supplier relationship attributes. Modelling the satisfactory level of dyadic relationship performance is very useful for identifying when the relationship begins to move away from the desired state. We then use the designed control chart to monitor the relationship between dyads over time to determine if any unusual behaviour has occurred (Phase II) and illustrate its implementation through a case study from the auto industry. This research illustrates how supply chain managers can secure and improve their supply chain performance by monitoring and maintaining strong relationships with their partners. The proposed method extends the existing SPC tools to effectively manage Type B buyer–supplier relationships.